Using qualitative methods to develop a survey measure of math and science engagement. (June 2016) - Fredricks, Jennifer A.; Wang, Ming-Te; Schall Linn, Jacqueline; Hofkens, Tara L.; Sung, Hannah; Parr, Alyssa; Allerton, Julia
Abstract: Student engagement in math and science is vital to students' academic achievement and long-term participation in science, technology, engineering, and mathematic (STEM) courses and careers. In this study, we conducted in-depth interviews with 106 students from sixth to twelfth grade and 34 middle and high school teachers about how they conceptualized math and science engagement and disengagement. Our qualitative analysis of student and teacher interviews supported the multidimensional construct of engagement outlined in the academic literature. Our analysis also revealed additional indicators that have been included in prior measures of engagement less frequently. We then described how we used this qualitative information from students and teachers to develop and validate a new student self-report measure of math and science engagement. Highlights: Teachers and students conceptualize engagement as a multidimensional construct. Our qualitative methodology confirms existing indicators of engagement. We identified additional items that reflect engagement in math and science. Our engagement measure includes a social engagement dimension.